Servants of God papers on the use of full-time workers in Brethren churches - Rowdon, Harold H.; Christian Brethren Research Fellowship, UK (Exeter, UK Paternoster, 1986)
Contents : INTRODUCION / Gerald West -- PART ONE, WHERE WE ARE NOW: The Brown-Pearce survey / Roger Pearce -- The present position / Brian Mills -- The historical perspective / Harold Rowden -- PART TWO, WHAT THE BIBLE TEACHES: Biblical practices and principles / John Baigent -- Biblical reflections on the religious professional / David Clines -- PART THREE, HOW IT WORKS OUT: The role and status of a full-time worker / Neil Summerton --Patterns of full-time congretational ministry / Neil Summerton -- Adapting to full-time congregational ministry / Neil Summerton -- Full-time or part-time? / Alfred Kuen -- a local church view / Gerald West -- A personal view / Colin Holmes APPENDICES Selection and terms of service / Chris Bocutt -- Self-employed or employed? / Alec McIlhinney -- Impact on itinerant ministries / Stephen Short -- Impact on para-church ministries / Roger Chilvers -- The wife of the full-time worker / Rosemary Jennings -- Relationships within a group leadership / John Boyes. Includes bibliographical references.
Keywords: Brethren movement -- full-time workers